How Digitalization of Human Resource Management Empowers Enterprises' Innovation and Entrepreneurship Practices - Biao Zhang; Xiaonan Lv; Binhong Chen; Ting Li; Binbin Huang (Journal of Frontier in Economic and Management Research, 2025)
Amid the vigorous development of the digital economy, enterprises' innovation and entrepreneurship practices are facing unprecedented opportunities and challenges. During digital transformation, enterprises need to innovate human resource management (HRM) in multiple aspects. As a crucial link in enterprises' digital transformation, the digitalization of HRM is gradually becoming a core driving force for promoting enterprises' innovation and entrepreneurship. This paper deeply explores how the digitalization of HRM provides comprehensive support and guarantee for enterprises' innovation and entrepreneurship practices by innovating talent recruitment and selection mechanisms, optimizing talent training and development systems, improving performance management and incentive mechanisms, and constructing innovative organizational culture and team collaboration models. Combining theoretical analysis with practical cases, it reveals the important role of HRM digitalization in enhancing enterprises' innovation capabilities and stimulating employees' entrepreneurial spirit, and provides useful references for enterprises to achieve sustainable development.